2019
DOI: 10.1039/c9cp00984a
|View full text |Cite
|
Sign up to set email alerts
|

Pretransitional behavior of viscoelastic parameters at the nematic to twist-bend nematic phase transition in flexiblen-mers

Abstract: We report dynamic light scattering measurements of the orientational (Frank) elastic constants and associated viscosities among a homologous series of a liquid crystalline dimer, trimer, and tetramer exhibiting a uniaxial nematic (N) to twist-bend nematic (NTB) phase transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…35 To date, a number of bent LC dimers composed of two mesogenic structures connected with an odd-numbered oligomethylene spacer have been shown to exhibit the N TB phase. In addition, several LC oligomers (e.g., trimers, 53,[58][59][60][61][62][63] tetramers, 58,59,64 a hexamer, 65 and other types of oligomers [66][67][68][69] ), polymers, 70 and bent-core molecules 71,72 have also been identified as twist-bend nematogens. It should be noted here that the bent molecular geometry is key to designing twist-bend nematogens.…”
Section: Introductionmentioning
confidence: 99%
“…35 To date, a number of bent LC dimers composed of two mesogenic structures connected with an odd-numbered oligomethylene spacer have been shown to exhibit the N TB phase. In addition, several LC oligomers (e.g., trimers, 53,[58][59][60][61][62][63] tetramers, 58,59,64 a hexamer, 65 and other types of oligomers [66][67][68][69] ), polymers, 70 and bent-core molecules 71,72 have also been identified as twist-bend nematogens. It should be noted here that the bent molecular geometry is key to designing twist-bend nematogens.…”
Section: Introductionmentioning
confidence: 99%
“…In-depth reinvestigation of an LC dimer comprising two 4cyanobiphenyl arms connected by a heptamethylene spacer, 1ʺ,7ʺ-bis(4-cyanobiphenyl-4ʹ-yl)heptane (CB7CB) indicated that the Nx phase is the NTB phase [11] (here, it is to be noted that the Nx phase observed for the tetrapod molecule reported recently by Mandle et al was distinguished from the NTB phase [7]). Thus, identification of the NTB phase inspired extensive study on a large number of molecules that exhibit the NTB phase, such as bent LC dimers , various oligomers [35,[37][38][39][40][41][42][43][44][45][46], polymers [47], and bent-core molecules [48,49], and on related potential applications [50][51][52][53][54]. Electro-optical analysis [55], transmission electron microscopy [56,57], and soft, tender, and hard resonant X-ray scattering [34,[58][59][60][61] confirmed that the helical pitch of the NTB phase is considerably short, typically the length of several molecules or 10-20 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Substituting Eq. (31), (32), and (33) into Eq. (30), we get v L ∂ γ Q αβ r ð Þ∂ γ Q αβ r ð Þ ¼ 9 2 S 2 L q 2 sin 2 ε e k 2 sin 2 ε þ e k 3 1−sin 2 ε…”
Section: Appendix: Determination Of Distortion Free Energy (F Dis )mentioning
confidence: 99%
“…The k 3 shows unusual temperature dependences. When temperature is decreased, k 3 first increases, after crossing the I-N transition, then dips in the vicinity of N-N TB transition, and finally increases again as the transition is crossed [7,8,32].…”
Section: Introductionmentioning
confidence: 99%